2020
DOI: 10.3389/fonc.2020.558306
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Factor V Is an Important Determinant of the Metastatic Potential of Circulating Tumor Cells

Abstract: Factor V (FV) is a critical component in the blood coagulation cascade. In patients, FV inhibitors have been reported to be associated with malignancy. FV is present in plasma and platelets, which exhibit physical and functional differences. However, the functions of FV in cancer progression remain poorly understood. We evaluated the impact of different levels of FV in plasma and platelets on the haematogenous mouse pulmonary metastasis model to determine whether FV determines the metastatic potential of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Interestingly, variations in the haematocrit can modulate the adhesion of CTC to the vessel wall, their velocity in the blood flow and red blood cell aggregation 28 . Similarly, factors of the coagulation cascade, as factor V, have demonstrated a role in the interaction of the CTC with the vascular endothelium and the efficiency of metastasis 29 . From a therapeutic perspective, anticoagulant drugs as low molecular weight heparin and warfarin, contributing to reduce blood viscosity, have shown antitumor and antimetastatic activity 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, variations in the haematocrit can modulate the adhesion of CTC to the vessel wall, their velocity in the blood flow and red blood cell aggregation 28 . Similarly, factors of the coagulation cascade, as factor V, have demonstrated a role in the interaction of the CTC with the vascular endothelium and the efficiency of metastasis 29 . From a therapeutic perspective, anticoagulant drugs as low molecular weight heparin and warfarin, contributing to reduce blood viscosity, have shown antitumor and antimetastatic activity 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Individual CTC detachment from the ECM may also induce anoikis that can be overcome by tight junction maintenance in circulating clusters [36]. Several recent studies have shown that hyper-activated platelets adhere to CTC clusters and secrete soluble effectors conferring enhanced survival properties and increased metastatic efficiency to CTCs [37][38][39][40]. In this context, Yu and colleagues described that platelet-tumor cell interaction through Toll-like receptor 4 (TLR4) promotes tumor metastasis [41].…”
Section: The Circulating Tumor Cellmentioning
confidence: 99%